New Insights into the Complex Relationship between Weight and Maturity of Burgundy Truffles (Tuber aestivum) - Büntgen, Ulf; Bagi, István; Fekete, Oszkár; Molinier, Virginie; Peter, Martina; Splivallo, Richard; Vahdatzadeh, Maryam; Richard, Franck; Murat, Claude; Tegel, Willy; Stobbe, Ulrich; Martínez-Peña, Fernando; et al. (PloS one, 2017)
Despite an increasing demand for Burgundy truffles (Tuber aestivum), gaps remain in our understanding of the fungus' overall lifecycle and ecology. Here, we compile evidence from three independent surveys in Hungary and Switzerland. First, we measured the weight and maturity of 2,656 T. aestivum fruit bodies from a three-day harvest in August 2014 in a highly productive orchard in Hungary. All specimens ranging between 2 and 755 g were almost evenly distributed through five maturation classes. Then, we measured the weight and maturity of another 4,795 T. aestivum fruit bodies harvested on four occasions between June and October 2015 in the same truffière. Again, different maturation stages occurred at varying fruit body size and during the entire fruiting season. Finally, the predominantly unrelated weight and maturity of 81 T. aestivum fruit bodies from four fruiting seasons between 2010 and 2013 in Switzerland confirmed the Hungarian results. The spatiotemporal coexistence of 7,532 small-ripe and large-unripe T. aestivum, which accumulate to ~182 kg, differs from species-specific associations between the size and ripeness that have been reported for other mushrooms. Although size-independent truffle maturation stages may possibly relate to the perpetual belowground environment, the role of mycelial connectivity, soil property, microclimatology, as well as other abiotic factors and a combination thereof, is still unclear. Despite its massive sample size and proof of concept, this study, together with existing literature, suggests consideration of a wider ecological and biogeographical range, as well as the complex symbiotic fungus-host interaction, to further illuminate the hidden development of belowground truffle fruit bodies.
Keywords: plodnice hub; Switzerland; Hungary; stadia vývoje; Ascomycota; Švýcarsko; Fruiting Bodies, Fungal; symbióza; Life Cycle Stages; Soil; Maďarsko; půda; Symbiosis